2017
DOI: 10.1159/000480531
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin and Curcumin Synergistically Induce Apoptosis in SKOV3 Cells Via Upregulation of MiR-124 Targeting Midkine

Abstract: Background/Aim: Women with advanced ovarian carcinoma are less likely to receive platinum-based chemotherapy and surgery due to a greater risk of cytotoxicity and poorer outcomes. We attempted to improve a promising therapy against ovarian cancer by using a combination of dihydroartemisinin (DHA) and curcumin (Cur). Methods: Human ovarian cancer SKOV3 cells were treated with DHA, Cur alone, or a combination of both. The viability of SKOV3 cells was measured by Cell Counting Kit-8 (CCK-8) and a colony formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 35 publications
(28 reference statements)
1
21
0
Order By: Relevance
“…The data demonstrated that DHA synergizes with rapamycin and promotes cell death and apoptosis via the upregulation of DAPK and Atg7, which provides an indication for its usefulness in anticancer studies and clinical application. In accordance with the results of other studies regarding DHA, the effects of DHA on autophagy were further confirmed (28)(29)(30)(31)(32). The present study provides novel evidence regarding the effects of rapamycin combined with DHA and Atg7 knockdown; however, owing to the limitations of in vitro experiments, the associated combined effects should be investigated in in vivo animal models in the future, with further cell lines investigated.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The data demonstrated that DHA synergizes with rapamycin and promotes cell death and apoptosis via the upregulation of DAPK and Atg7, which provides an indication for its usefulness in anticancer studies and clinical application. In accordance with the results of other studies regarding DHA, the effects of DHA on autophagy were further confirmed (28)(29)(30)(31)(32). The present study provides novel evidence regarding the effects of rapamycin combined with DHA and Atg7 knockdown; however, owing to the limitations of in vitro experiments, the associated combined effects should be investigated in in vivo animal models in the future, with further cell lines investigated.…”
Section: Discussionsupporting
confidence: 90%
“…Zhao et al (32) demonstrated that combined treatment with DHA and curcumin decreased cell viability, arrested the cell cycle and promoted apoptosis in human ovarian cancer SKOV3 cells. It was also identified that treatment with DHA alone has the ability to induce limited apoptosis, arrest the cell cycle at the S and G 2 /M phases and inhibit tumor growth in a xenograft model established by subcutaneously injecting SKOV3 cells into the right flank of female BALB/c nude mice, without notable toxicity (32). Additionally, caspase-3 was not activated following treatment with DHA, and caspase-3 inhibitors did not inhibit cell apoptosis in any group; therefore, it was hypothesized that DHA may induce cell apoptosis via other apoptotic pathways (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports in the literature show that the anti-tumor effects of curcumin include not only the inhibition of tumor cell proliferation but also the induction of apoptosis [28]. Thus, we further tested whether LC could induce the apoptosis of EC cells.…”
Section: Discussionmentioning
confidence: 97%
“…The overexpression of miR-214 was reported in gastric [27] and cervical cancers [28, 29]. However, in most cases, miR-214 was downregulated and exerted an anti-oncogenic role [30-33]. For example, miR-214 suppressed the cell proliferation, migration, and invasion by targeting MEK3, JNK1, Plexin-B1, and GALNT7 [29, 34, 35] in cervical cancer cells.…”
Section: Introductionmentioning
confidence: 99%